Early-onset familial hemiplegic migraine due to a novel SCN1A mutation. (November 2016) - Fan, Chunxiang; Wolking, Stefan; Lehmann-Horn, Frank; Hedrich, Ulrike BS; Freilinger, Tobias; Lerche, Holger; Borck, Guntram; Kubisch, Christian; Jurkat-Rott, Karin
Introduction: Familial hemiplegic migraine (FHM) is a rare autosomal dominant subtype of migraine with aura. The FHM3 subtype is caused by mutations in SCN1A, which is also the most frequent epilepsy gene encoding the voltage-gated Na + channel NaV 1.1. The aim of this study was to explore the clinical, genetic and pathogenetic features of a pure FHM3 family. Methods: A three-generation family was enrolled in this study for genetic testing and assessment of clinical features. Whole cell patch-clamp was performed to determine the functions of identified mutant NaV 1.1 channels, which were transiently expressed in human tsA201 cells together with β1 and β2 subunits. Results and conclusions: We identified a novel SCN1A (p.Leu1624Pro) mutation in a pure FHM family with notably early-onset attacks at mean age of 7. L1624P locates in S3 of domain IV, the same domain as two of four known pure FHM3 mutations. Compared to WT channels, L1624P displayed an increased threshold-near persistent current in addition to other gain-of-function features such as: a slowing of fast inactivation, a positive shift in steady-state inactivation, a faster recovery and higher channel availability during repetitive stimulation. Similar to the known FHM3 mutations, this novel mutation predicts hyperexcitability of GABAergic inhibitory neurons.